2010
DOI: 10.1007/jhep09(2010)091
|View full text |Cite
|
Sign up to set email alerts
|

Observation of long-range, near-side angular correlations in proton-proton collisions at the LHC

Abstract: Results on two-particle angular correlations for charged particles emitted in proton-proton collisions at center-of-mass energies of 0.9, 2.36, and 7TeV are presented, using data collected with the CMS detector over a broad range of pseudorapidity (eta) and azimuthal angle (phi). Short-range correlations in Delta(eta), which are studied in minimum bias events, are characterized using a simple "independent cluster" parametrization in order to quantify their strength (cluster size) and their extent in eta (clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
554
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 722 publications
(622 citation statements)
references
References 34 publications
46
554
3
4
Order By: Relevance
“…After the penalty factors which we have enumerated are included, the estimated cross-section for the collision of aligned flux tubes is reduced to a value in the neighborhood of 1 microbarn. This is quite similar to the cross section for events with a trigger of more than 110 charged-particle tracks used in the CMS experimental 'ridge' analysis [1].…”
Section: Consequences Of the Collisions Of Oriented Qcd Flux Tubessupporting
confidence: 72%
See 2 more Smart Citations
“…After the penalty factors which we have enumerated are included, the estimated cross-section for the collision of aligned flux tubes is reduced to a value in the neighborhood of 1 microbarn. This is quite similar to the cross section for events with a trigger of more than 110 charged-particle tracks used in the CMS experimental 'ridge' analysis [1].…”
Section: Consequences Of the Collisions Of Oriented Qcd Flux Tubessupporting
confidence: 72%
“…We have suggested that the ridge-like correlation found by the CMS collaboration [1,2] in high-multiplicity events in pp collisions at the LHC could be evidence for the collision of aligned high-intensity flux tubes connecting the valence quarks of the colliding protons. A key property is the correlation of ridge events between positive and negative rapidity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Amazingly, similar correlations were discovered in 2010 at the LHC in high multiplicity events produced in pp collisions at 7 TeV [2] and, some time later, also in pPb collisions, raising questions about the possible common nature of the systems formed in pp, pA and AA collisions.…”
Section: Introductionmentioning
confidence: 62%
“…6. The normalized SC (2,3) values are found to be very similar between pPb and PbPb systems at high multiplicities. Taken together with the v n results in Fig.…”
Section: Multiparticle Azimuthal Correlations With Symmetric Cumulantsmentioning
confidence: 81%